THE PROFOUND CHARACTERISTICS OF EFFECTIVE TEACHING ENGLISH TO THE STUDENTS IN THE FIELD OF INTERNATIONAL RELATIONS - Djuraev, Abdulkhay (Educational Research in Universal Sciences, 2023)
This article focuses on the important role of English language instruction in international relations. Effective teaching in this field promotes global communication and understanding. The study highlights the characteristics of a skilled teacher and emphasizes the need for inclusive learning environments that meet the specific needs of international relations students. By incorporating real-world relevance, diverse teaching methods, and fostering empathy and adaptability, educators play a crucial role in shaping individuals who possess both language skills and cultural understanding necessary for navigating the complexities of the global stage. The article aims to explore the complexities of this teaching approach and the connection between language instruction and the development of future leaders in international relations.